Ultimate Guide To Sex And Disability: For All Of Us Who Live With Disabilities, Chronic Pain, And Illness - Miriam Kaufman, Cory Silverberg & Fran Odette
The Ultimate Guide to Sex and Disability is the first complete sex guide for people who live with disabilities, pain, illness, or chronic conditions. Useful for absolutely everyone, regardless of age, gender, or sexual orientation, the book addresses a wide range of disabilities -- from chronic fatigue, back pain, and asthma to spinal cord injury, hearing and visual impairment, multiple sclerosis, and more. Expertly written by a medical doctor, a sex educator, and a disability activist, The Ultimate Guide provides readers with encouragement, support, and all the information they need to create a sex life that works for them. The authors cover all aspects of sex and disability, including building a positive sexual self-image; positions to minimize stress and maximize pleasure; dealing with fatigue or pain during sex; finding partners and talking with partners about sex and disability; adapting sex toys; and more.